2011
DOI: 10.1159/000331742
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular Permeability of Bronchial Epithelium is Controlled by CFTR

Abstract: In normal airway epithelium, the cystic fibrosis transmembrane conductance regulator (CFTR) transports Cl- ions to the apical surface of the epithelium paralleled by the flow of water through transcellular and paracellular pathways. The hypothesis was tested whether CFTR not only regulates the transcellular but also the paracellular shunt pathway. Therefore, we performed measurements of transepithelial electrical resistance (TER) and paracellular 14C-mannitol permeability in wtCFTR (16HBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
6
27
2
Order By: Relevance
“…A previous report showed delayed differentiation and regeneration in non-infected human CF nasal epithelia (Hajj et al, 2007). In the present study, the lower TER that we observed after CFTR inhibition or knockdown in epididymal cells is in agreement with the modulation of paracellular permeability by CFTR previously reported in cultured airway epithelial cells (Castellani et al, 2012;LeSimple et al, 2010;Nilsson et al, 2010;Weiser et al, 2011). In these studies, several mechanisms were proposed to mediate the regulation of the paracellular pathway by apical membranebound CFTR, including the participation of NHERF1, ezrin, the RhoA-ROCK pathway, myosin II and tyrosine kinase phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…A previous report showed delayed differentiation and regeneration in non-infected human CF nasal epithelia (Hajj et al, 2007). In the present study, the lower TER that we observed after CFTR inhibition or knockdown in epididymal cells is in agreement with the modulation of paracellular permeability by CFTR previously reported in cultured airway epithelial cells (Castellani et al, 2012;LeSimple et al, 2010;Nilsson et al, 2010;Weiser et al, 2011). In these studies, several mechanisms were proposed to mediate the regulation of the paracellular pathway by apical membranebound CFTR, including the participation of NHERF1, ezrin, the RhoA-ROCK pathway, myosin II and tyrosine kinase phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…32 While the role of CFTR in the transcellular transport of ions is well known, its the role in paracellular permeability and gate function of the airway epithelium is less known but is at present an intensive field of investigation. [33][34][35] Although we did not analyse here the role of NHERF1 and CFTR in the paracellular permeability to ions, our results are in line with those obtained by LeSimple et al, 33 who demonstrated that the presence of membrane CFTR is required for normal epithelial gate function, and with Weiser et al, 35 who recently showed that CFBE cell monolayers exhibit a higher paracellular permeability and lower TER (as in our study here) as compared with 16HBE monolayers. In particular, LeSimple et al 33 argued that CFTR trafficking is required for the normal organisation and function of TJs, although the increase in gate function upon overexpression of CFTR was not affected by the CFTR inhibitor CFTR inh -172 or lowchloride medium, implying that the effect of CFTR on TJ function was unrelated to its ion channel activity.…”
Section: Tight Junction Regulation In Cystic Fibrosissupporting
confidence: 92%
“…This observation may be coupled with the coaxing of CFTR to the plasma membrane and reduction in its turnover (ie, longer permanence of CFTR at this level) induced by NHERF1 overexpression demonstrated by us, 15 although we do not know the effect of CFTR inhibition on the resumption of TJ permeability defect in CFBE cells upon NHERF1 overexpression. On the same line, Weiser et al 35 showed that while cAMP induced an increase of paracellular permeability Tight junction regulation in cystic fibrosis S Castellani et al in 16HBE cells, in contrast CFBE cells respond to cAMP stimulation with a decrease of paracellular permeability paralleled by slight increase of TER, indicating that there is a link between CFTR dysfunction and an improper regulation of the paracellular transport route. Finally, Nilsson et al 34 tried to link paracellular ion transport, CFTR activity, and cellular cytoskeleton organisation.…”
Section: Tight Junction Regulation In Cystic Fibrosismentioning
confidence: 93%
“…The exact mechanism by which CFTR modulates epithelial permeability remains unclear. Weiser and colleagues (7) demonstrated that CFTR modulates phosphorylation of MLCK, and changes in paracellular permeability can be blocked by ML-7. However, ML-7 had no effect on b 2 -agonist-mediated increases of epithelial permeability in our studies.…”
Section: Resultsmentioning
confidence: 99%
“…These observations point to a significant contribution of the paracellular space for fluid transport. A number of reports have shown that CFTR controls paracellular permeability of bronchial epithelia (5)(6)(7), placing CFTR at a critical juncture in ASL volume regulation. In CF, mutations of the gene encoding CFTR are associated with a significant decrease in epithelial Cl 2 secretion, excessive Na 1 absorption (8), and decreased paracellular permeability (5,6).…”
mentioning
confidence: 99%